Reconstructing Global Health Law Post-Pandemic: Juridical Analysis of IPR and Equitable Access under WHO Pandemic Treaty - Salma Farha Nabila; Lasmin Alfies Sihombing; Yeni Nuraeni; Yenny Febrianty (Law Development Journal, 2026)
This study examines the juridical architecture of global health law in the post-pandemic context, focusing on the tension between intellectual property rights (IPR) protection and equitable access to medical resources. The COVID-19 pandemic exposed structural weaknesses and inequalities in global health governance, particularly in the distribution of vaccines and essential medical technologies. This research aims to analyze how the evolving WHO Pandemic Treaty framework can serve as an integrative legal instrument to reconcile these competing interests. The study employs a normative juridical method using statutory, conceptual, and case-based approaches, supported by qualitative legal analysis and the IRAC method to structure legal reasoning. The findings reveal that the current global health law architecture remains dominated by the IPR regime, which prioritizes innovation protection but inadequately ensures equitable access, especially for developing countries. Furthermore, mechanisms such as TRIPS flexibilities have not been effectively operationalized due to political, structural, and institutional constraints. The study also finds that global responses during the pandemic were shaped by power asymmetries and economic capacity rather than public health needs, leading to systemic inequities. As a novel contribution, this research highlights the potential of the WHO Pandemic Treaty as a transformative legal framework capable of integrating distributive justice principles, strengthening IPR flexibilities, and establishing binding obligations for equitable access. However, its effectiveness depends on robust normative design, enforceability mechanisms, and sustained political commitment from member states.